PENGARUH AMBIGUITAS PERAN TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI USAHA KECIL DAN MENENGAH (UKM) KABUPATEN BIMA - Eti Kurniati; Kusumayadi, Firmansyah (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the significant effect of role ambiguity on employee performance at the Department of Small and Medium Enterprises Cooperatives, Bima Regency. The instrument in this study used a questionnaire with a Likert scale. The population in this study were all employees at the Office of Cooperatives for Small and Medium Enterprises, Bima Regency, totaling 51 people consisting of 30 Civil Servants and 21 Honorary Employees. The sampling technique in this study was done by purposive sampling technique. Data collection techniques using observation, interviews, questionnaires, documentation. The data analysis technique used validity test, reliability test, simple linear regression test, simple correlation coefficient test, coefficient of determination test and t test with the help of SPSS version 22 for windows. The results showed that role ambiguity had a significant effect on employee performance at the Department of Cooperatives, Small and Medium Enterprises, Bima Regency.